Peran Pendidikan Islam dalam Membentuk Karakter Anti-LGBT Berdasarkan Perspektif Fiqih - Aprilia Indah Anggriani; Fadlil Muhammad Azhar; Muhammad Rizki; Wahyu Kurniawan; Intan Dwi Astutik (Halaqatuna, 2026)
The development of LGBT discussions and actions among the current generation poses a major challenge to values-based education, especially among Muslim communities in Indonesia. This issue is not only related to personal morality, but also affects social and cultural aspects, as well as the sustainability of the basic human values that form the foundation of Islamic teachings. In this regard, Islamic education is often noted as a normative solution, but it is still commonly understood in general terms and is often not explained in a systematic academic manner. The purpose of this study is to examine how Islamic education plays a role in shaping a character that rejects LGBT using a fiqh perspective, as well as to formulate a concrete definition of Islamic education as a system that includes objectives, content, methods, and practices of moral guidance. This study applies a descriptive qualitative approach through a literature review, which involves analyzing various literature on Islamic education, fiqh, and maqāṣid al-syarī‘ah. The findings of this study indicate that Islamic education is not merely cognitive religious instruction, but also a process in which the values of faith, worship, and morals are internalized through the Islamic Religious Education (IRE) curriculum, the teaching of faith and morals, the example set by educators, religious customs, and cooperation between families and communities. From a fiqh perspective, character building that rejects LGBT is based on the protection of maqāṣid al-syarī‘ah, especially hifẓ al-nasl and hifẓ al-akhlāq, by instilling the values of iffah, self-control (mujāhadah al-nafs), and awareness of fitrah. This study emphasizes the importance of strengthening Islamic education that is preventive, educational, and focused on character in order to face today's moral challenges, while also providing a clearer conceptual basis for the development of Islamic education policies and practices in Indonesia.